An Experimental Work on Multi-Roller Burnishing Process on Difficult to Cut Material – Titanium Alloy - Thamizhmanii, S.; Hassan, S. (International Journal of Integrated Engineering, 2009)
Burnishing is a cold working and chipless machining carried out to improve surface roughness, surface hardness, fatigue, compressive stress and corrosion resistance by using sliding speed, feed rate and depth of penetration. The process smooth out peaks valleys on the surface. This paper described the process carried out by multi-roller burnishing fitted in housing and rotated freely in a horizontal axis. The work material used was Titanium alloy Ti-6Al -4V. The process produced good surface roughness and hardness at high rotation of spindle coupled with high feed rate and high depth of penetration.